2020
DOI: 10.1016/j.ygyno.2020.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Supported self-management as a model for end-of-life care in the setting of malignant bowel obstruction: A qualitative study

Abstract: Advanced cancer patients with severe symptoms and rapid terminal trajectories are able to participate in self-management.• Interventions that support patients in self-management can reduce physical, psychological, and existential distress.• Such interventions also facilitate care at home rather than in hospital, and may reduce inpatient stays at the end-of-life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 34 publications
(56 reference statements)
0
34
0
Order By: Relevance
“… 34 Three other papers described the symptoms of malignant bowel obstruction in less detail but highlighted the debilitating and distressing impact that symptoms had on both patients and families, particularly symptoms of pain, nausea, and vomiting. 26 , 27 , 29 For example, nurses interviewed 27 in one study identified the far-reaching impacts of these distressing symptoms on not just the patient, but their family members also: “They have pain, discomfort, nausea, vomiting and transcends to the families.” Nurse, page 596 . 27 One patient described the pain they experienced as an endless, debilitating feeling “very painful.…”
Section: Resultsmentioning
confidence: 99%
“… 34 Three other papers described the symptoms of malignant bowel obstruction in less detail but highlighted the debilitating and distressing impact that symptoms had on both patients and families, particularly symptoms of pain, nausea, and vomiting. 26 , 27 , 29 For example, nurses interviewed 27 in one study identified the far-reaching impacts of these distressing symptoms on not just the patient, but their family members also: “They have pain, discomfort, nausea, vomiting and transcends to the families.” Nurse, page 596 . 27 One patient described the pain they experienced as an endless, debilitating feeling “very painful.…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al provided patients with education on MBO symptoms and diagnosis, as well as frequent check-ins after discharge home [14]. A qualitative analysis showed that patients valued these interventions, and their daily concerns and changes in symptoms could be managed outpatient by an expert team, to prioritize their ability to be home [6].…”
Section: Discussionmentioning
confidence: 99%
“…Literature on MBO prognosis and interventions shows a median survival after MBO ranging between one and six months [1] [2] [3] [4] [5]. However, qualitative studies have shown that it is not always clear to ovarian cancer patients that a MBO is a turning point of disease trajectory and prognosis [6]. There is a gap between the medical data available and the patient understanding of MBO.…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative study described the benefits of a model of supported self-management for women with advanced gynecological cancers and MBO attending out-patient clinics. Clear communication, counselling and referral to early palliative care were identified as important considerations [144]. A separate qualitative study with oncologists treating gynecological cancers identified that early palliative care referral was beneficial, particularly in situations where patients were not candidates for surgery [145].…”
Section: Psychosocial Supportmentioning
confidence: 99%